The efficacy of micro‐insulated needle radiofrequency system for the treatment of lower eyelid fat bulging - Shin, Jung‐Won; Park, Jung‐Tae; Chae, Je‐Byeong; Choi, Ji‐Young; Na, Jung‐Im; Park, Kyoung‐Chan; Huh, Chang‐Hun (Journal der Deutschen Dermatologischen Gesellschaft, 2019)
Summary Background and objectives Conventional treatment options for eyelid fat bulging are generally limited to surgical approaches. However, many attempts have been made recently to manage this disfigurement using non‐surgical interventions. The purpose of this study was to evaluate the efficacy and safety of a micro‐insulated needle radiofrequency system for the treatment of lower eyelid fat bulging. Methods This is a single center pre‐post comparative study. Twenty‐two subjects with lower eyelid fat bulging were treated twice using the needle radiofrequency system, at an interval of four weeks. Two types of partially insulated needles with different lengths were used in each session. A three‐dimensional photogrammetry system was used to objectively measure changes in the extent of the fat bulge. The investigator's global assessment (IGA) of the severity of fat bulging was also evaluated. Results The average extent of fat bulging was decreased significantly after twelve weeks, and was maintained until 24 weeks. The IGA score was significantly decreased after four weeks and further decreased after twelve weeks, and then maintained until 24 weeks. There were no side effects, except for lower eyelid swelling and bruising that lasted for about a week. Conclusion The micro‐insulated needle radiofrequency system can be a beneficial and well‐tolerated treatment for lower eyelid fat bulging.